Peroxisome Proliferator-Activated Receptor Activation in Precision-Cut Bovine Liver Slices Reveals Novel Putative PPAR Targets in Periparturient Dairy Cows - Busato, Sebastiano; Ford, Hunter R.; Abdelatty, Alzahraa M.; Estill, Charles T.; Bionaz, Massimo (Frontiers in Veterinary Science, 2022)
Metabolic challenges experienced by dairy cows during the transition between pregnancy and lactation (also known as peripartum), are of considerable interest from a nutrigenomic perspective. The mobilization of large amounts of non-esterified fatty acids (NEFA) leads to an increase in NEFA uptake in the liver, the excess of which can cause hepatic accumulation of lipids and ultimately fatty liver. Interestingly, peripartum NEFA activate the Peroxisome Proliferator-activated Receptor (PPAR), a transcriptional regulator with known nutrigenomic properties. The study of PPAR activation in the liver of periparturient dairy cows is thus crucial; however, current in vitro models of the bovine liver are inadequate, and the isolation of primary hepatocytes is time consuming, resource intensive, and prone to errors, with the resulting cells losing characteristic phenotypical traits within hours. The objective of the current study was to evaluate the use of precision-cut liver slices (PCLS) from liver biopsies as a model for PPAR activation in periparturient dairy cows. Three primiparous Jersey cows were enrolled in the experiment, and PCLS from each were prepared prepartum (−8.0 ± 3.6 DIM) and postpartum (+7.7± 1.2 DIM) and treated independently with a variety of PPAR agonists and antagonists: the PPARα agonist WY-14643 and antagonist GW-6471; the PPARδ agonist GW-50156 and antagonist GSK-3787; and the PPARγ agonist rosiglitazone and antagonist GW-9662. Gene expression was assayed through RT-qPCR and RNAseq, and intracellular triacylglycerol (TAG) concentration was measured. PCLS obtained from postpartum cows and treated with a PPARγ agonist displayed upregulation of ACADVL and LIPC while those treated with PPARδ agonist had increased expression of LIPC, PPARD, and PDK4. In PCLS from prepartum cows, transcription of LIPC was increased by all PPAR agonists and NEFA. TAG concentration tended to be larger in tissue slices treated with PPARδ agonist compared to CTR. Use of PPAR isotype-specific antagonists in PCLS cultivated in autologous blood serum failed to decrease expression of PPAR targets, except for PDK4, which was confirmed to be a PPARδ target. Transcriptome sequencing revealed considerable differences in response to PPAR agonists at a false discovery rate-adjusted p-value of 0.2, with the most notable effects exerted by the PPARδ and PPARγ agonists. Differentially expressed genes were mainly related to pathways involved with lipid metabolism and the immune response. Among differentially expressed genes, a subset of 91 genes were identified as novel putative PPAR targets in the bovine liver, by cross-referencing our results with a publicly available dataset of predicted PPAR target genes, and supplementing our findings with prior literature. Our results provide important insights on the use of PCLS as a model for assaying PPAR activation in the periparturient dairy cow.